ANALISIS WACANA IKLAN KOSMETIK DI MEDIA TELEVISI - Sumasari, Yoani Julita (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
In this research, discusses the analysis of discourse in cosmetics advertising on television. The data were analyzed in form of discourses contained of advertisements on television as much as 30 advertisements. Based on the theory used in this research include the theory of discourse analysis. This research classified in descriptive qualitative research. The data collection methods used techniques of listening and writing down techniques. The results of the data analysis indicate that aspects of language contained in persuasive discourse in television advertising in form of repetition of words, repetition of sentences, using interesting vocabulary, and the use of the term of interest, while aspects such as unlanguages, accuracy of talking with the speaker, precision timing and how to delivery through tones. The expected effects of the audience not only interested but trustworthly that the advertised product is suitable for the audience and make them want to buy then use them. Keywords: discourse analysis, cosmetic advertisement, television.